What is the most useful tool in HPV vaccine promotion? Results from an experimental study - Maria Rosaria Gualano; Robin Thomas; Michela Stillo; Maria Valentina Mussa; Francesca Quattrocolo; Alberto Borraccino; Carla Zotti (Taylor & Francis Group, 2019)
Introduction: Human papillomavirus infection (HPV) affects 70-80% of female population throughout the lifetime, exposing them to the risk of developing genital warts and cervical cancer. Despite these correlated risks and the demonstrated efficacy of the vaccine, coverage rates for two-three doses are around 70% in Italy and 67% in Piemonte (below the expected 95%). Aim of the study is to investigate whether this situation is due to a lack of information and awareness among young adults. Results: Students showed increased knowledge after the intervention and more than 90% found the 3 informative materials as sources of useful information. After the intervention students would strongly recommend HPV vaccination (OR = 3.45; p < 0.001). Discussion: Higher rates of correct answers after the distribution of informative material underline the importance of knowledge delivery. Differences among the kind of material were reported; it appears that a combination of leaflet's positive features, such as clarity and intelligibility, and article's completeness of information represents the best solution to reach communication goals in vaccination campaigns targeted on educated populations. Methods: Researchers conducted an experimental study on a large population of undergraduate students from University of Turin. Participants' knowledge about HPV was assessed with questionnaires before and after the examination of 3 different kinds of informative material (journal article describing HPV infection, gynecologist video-interview and institutional leaflet about HPV prevention) on HPV and vaccine. Differences among groups were explored by using univariate tests, differences in pre- post- knowledge were assessed with McNemar tests. Relevant associations were searched with logistic regression models.